Participation in Higher Education System - Muradova, M. K. (European Journal of Life Safety and Stability (2660-9630), 2022)
Formation and development of concept of participational control in management is considered in the article. The essence of participation is defined. Levels of involvement of workers in management process are allocated. Orientation to participation in the educational process at the higher school is designated. Development of the concept “participation” in pedagogical science is presented.